การส่งเส้นประสาทจากบริเวณ 17 ของเนื้อหุ้มสมองส่วนนอกจาก Ganglion cells ของ Retina และจากเซลล์ชั้นต่าง ๆ ของสมองส่วน Superior collinulus : รายงานผลการวิจัย - จิตร สิทธิอมร (จุฬาลงกรณ์มหาวิทยาล้ย, 1975)
The differential projections of the superficial and deep layers of the superior colliculus have been investigated in 20 dogs. Micro-electrodes were advanced to the superior colliculus using stereotaxic apparatus. Simultaneous recording of action potentials responding to the contralateral visual stimulation was performed. The occurrence of visual response was used as a criteria indicating that the tip of the microelctrode was within the superficial layer of the superior colliculus. The electrode was advanced 250 micra downward to reach the deep layers. Direct current ranging from 30-5,000 microampere were passed to make lesions in the appropriate layers. After surgery the animals were allowed to survive 8-10 days. At the end of the survival time, each animal was perfused with neutral formalin under pressure. Serial frozen sections were obtained and alternate sections were stained either with cresyl violet or by the Fink-Heimer modification of the method of Nauta and Gygax to trace Wallerian degeneration. It was found that cells inn the superficial layers of the superior colliculus project to pretectal nucleus, pulvinar and lateral geniculate nucleus, all of which are generally believed to be visual structures. Cells in the deep layers, however, project to the inferior colliculus, medical geniculate nucleus, midbrain and pontine reticular formation - structures known to receive multimodal sensory input and /or capable of influencing motor and autonomic pattern of an organism. Degeneration studies after retinal and area 17 removal were performed prior to above study to determine the appropriate survival time used.